Fractional Dynamics of a System with Particles Subjected to Impacts - Tenreiro Machado, J. A. (2019)
This paper studies the dynamics of a system composed of a collection of particles that exhibit collisions between them. Several entropy measures and di erent impact conditions of the particles are tested. The results reveal a power law evolution both of the system energy and the entropy measures, typical in systems having fractional dynamics.